Batas Koersi Negara dan Hak Individu: Perbandingan Libertarianisme Robert Nozick dan Konstitusionalisme Islam Abdullahi Ahmed An-Naʿim - Raihan Aditya; Rahmat Hidayatullah; Bustamin Bustamin (Paradigma: Jurnal Kalam dan Filsafat, 2026)
This article compares Robert Nozick and Abdullahi Ahmed An-Naʿim on individual rights and the limits of state coercion. This library-based study employs a comparative conceptual analysis of Anarchy, State, and Utopia and Islam and the Secular State. The findings demonstrate that both thinkers restrict coercive state power, although they rely on different foundations and protect different domains. Nozick understands rights as side constraints grounded in self-ownership; the state may therefore neither impose redistributive arrangements nor pursue paternalistic objectives. An-Naʿim grounds rights in equal citizenship, constitutionalism, and human rights; the state may therefore not enforce religious doctrine as public law. Unlike Nozick’s minimal state, however, An-Naʿim retains a broader state role in protecting equality and social justice. The article identifies two models of limiting coercion: Nozick’s proprietary-rights model and An-Naʿim’s citizenship-rights model.